1994
DOI: 10.1152/jappl.1994.77.5.2169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in potential controllers of human skeletal muscle respiration during incremental calf exercise

Abstract: The purpose of this study was to evaluate the consequences of non-linear changes in phosphocreatine (PCr) and pH during incremental calf exercise on estimates of ADP and cytosolic free energy of ATP hydrolysis (delta GATP). Six subjects performed incremental plantar flexion exercise on a treadle ergometer while muscle P(i) metabolism (PCr, P(i), ATP) and pH were followed using 31P-nuclear magnetic resonance spectroscopy. Changes in ADP and delta GATP were estimated with the assumption that there was equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
51
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 0 publications
10
51
4
Order By: Relevance
“…The work rate is given between the vertical lines. Statistically significant effects were marked with * (P <0.001) 31 P-MRS studies reported intramuscular mean pH values between 7.0 and 7.1 (Barstow et al 1994a(Barstow et al , 1994bFrancescato et al 2003;Marsh et al 1991;Rossiter et al 2001Rossiter et al , 2002. Collectively, the intramuscular pH of our volunteers at rest ranged between 6.94 and 7.02.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The work rate is given between the vertical lines. Statistically significant effects were marked with * (P <0.001) 31 P-MRS studies reported intramuscular mean pH values between 7.0 and 7.1 (Barstow et al 1994a(Barstow et al , 1994bFrancescato et al 2003;Marsh et al 1991;Rossiter et al 2001Rossiter et al , 2002. Collectively, the intramuscular pH of our volunteers at rest ranged between 6.94 and 7.02.…”
Section: Discussionmentioning
confidence: 74%
“…However, the prediction of the PCr kinetics, when employing the time constants derived from the moderate exercise to the heavy exercise, resulted in an underestimation of PCr hydrolysis, indicating a non-linear metabolism during heavy exercises. Other previous studies have reported an acceleration of PCr hydrolysis during work rates above the lactate threshold (Barstow et al 1994b;Marsh et al 1991). The lactate threshold occurs in a range between 60 to 80% of the peak work rate, as determined by spectroscopic measurement during exhaustive progressive muscle exercises in several previous studies (Barstow et al 1994b;Marsh et al 1991;McCreary et al 1996;Schocke et al 2004a).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Kemp's presentation provides a clear and important reminder that, in vivo, pH is not constant during the transition from a low to a higher metabolic rate, because phosphocreatine (PCr) splitting is a net alkalinizing reaction, which is balanced or exceeded by acidifying reactions (1). Moreover, the in vivo temporal discrepancies in these acid/base responses can allow distinction among models of control of respiration that otherwise appear inseparable (1).…”
mentioning
confidence: 99%